O cuidado de pessoas com transtornos mentais no cotidiano de seus familiares: investigando o papel da internação psiquiátrica - Dalla Vecchia, Marcelo; Martins, Sueli Terezinha Ferreira [UNESP] (PPgPsi-UFRN, 2006)
As atribuições da família no cuidado de seus membros portadores de transtornos mentais têm passado por profundas transformações nos últimos anos. A presente pesquisa investigou as modificações no cotidiano de familiares de pessoas que passaram por internação psiquiátrica e os significados implicados neste processo. Foram realizadas entrevistas semi-estruturadas com cinco familiares, cujo conteúdo foi submetido à análise temática e interpretado em perspectiva sócio-histórica. Dentre outras questões, observa-se que: (1) a concepção de cura está relacionada à recuperação da capacidade produtiva, restrita a partir do surgimento dos sintomas; (2) os recursos informais são complementares, principalmente quando os recursos públicos não são suficientes ou satisfatórios; (3) a religiosidade está presente na compreensão metafísica das causas do sofrimento psíquico; (4) a igreja, na figura dos correligionários, consiste em um grupo de suporte para o usuário e para a sua família e (5) a insuficiência de políticas adequadas de atenção à família na rede substitutiva.

Family responsibilities on the care of their relatives suffering mental illnesses have passed through deep changes on the last years. The present study investigated the modifications of daily lives of relatives of people who lived long stay admission in psychiatric hospitals and the meanings implicated on this process. The content of semi-structured interviews carried along with five relatives was submitted to thematic analysis and interpreted in socio-historical perspective. Amongst other issues, it was possible to notice that: (1) healing conception is related to the recovery of productive abilities, restricted as long as the symptoms arise; (2) informal resources are complementary, specially when public resources are not enough or satisfactory; (3) religious issues are present in a metaphysical understanding of mental suffering; (4) the church and its representatives consist on a support group for the person and his/her family; and (5) adequate programs regarding family support in mental health open services are not enough.
Health care of people suffering of mental illnesses in their relatives' daily lives: investigating the role of long stay admission in psychiatric hospitals
Keywords: saúde mental; família; reabilitação psicossocial; psicologia sócio-histórica; mental health; family; psychosocial rehabilitation; social-historical psychology